A Review of Design Strategies and Material Challenges for Magnesium-Based Rechargeable Seawater Batteries: Insights from Sodium-RSB Systems - Rezza Ruzuqi; Agus Sigit Pramono; Lukman Noerochim (Journal of Multidisciplinary Applied Natural Science, 2026)
Rechargeable seawater batteries (RSBs) are a new class of seawater-based energy storage technology. In this system, the two electrolytes—the non-aqueous anolyte and seawater as the catholyte—have distinct compositions. As an eco-friendly option, the technology is promising, with the potential to replace traditional rechargeable batteries and reduce harmful environmental impacts. It can also be used in locales without access to power. There are different classes of RSBs, including sodium-based (Na-RSBs). At present, Na-RSBs systems have attracted much more attention due to the availability of solvents derived from abundant sodium sources in seawater and because of their superior material costs and safety compared to lithium (Li)-based batteries. Nonetheless, Na-RSBs are inherently restricted by the relatively low theoretical capacity and electrochemical potential of sodium. As a result, magnesium-based rechargeable seawater batteries (Mg-RSBs) have emerged as a promising alternative. Magnesium is attractive because it offers a higher theoretical volumetric capacity (~3833 mAh cm⁻³) and a better cost-performance ratio than Li-ion batteries and Na-RSB systems. Given these merits, we summarize the potential of magnesium as a candidate alternative to sodium in RSB applications. To develop their potential, some strategies (alloying, surface modification, bifunctional catalyst design, and solid–liquid hybrid electrolyte construction) are proposed. The perspective concludes with an outlook that emphasizes the importance of accounting for integrated electrolyte–separator design, interface manipulation, and corrosion-mitigation strategies to realize the potential of Mg-RSBs as a high-durability, long-life, and economical battery system, especially in off-grid applications.